Edukasi Gizi Tentang Anemia Pada Remaja Putri di SMA Negeri 1 Batang Kuis - Sihotang, Urbanus; Tarigan, Novriani (Shihatuna : Jurnal Pengabdian Kesehatan Masyarakat, 2024)
Iron deficiency anemia can have an impact on young women, such as getting tired quickly, reducing the body's resistance to infectious diseases, reducing body fitness, reducing concentration and learning achievement, reducing the immune system and disrupting physical growth. Iron deficiency anemia during adolescent girls in turn leads adolescent girls to anemia in later pregnancy.The aim of this activity is to increase knowledge about anemia so that teenage girls can prevent anemiaCommunity service implemented at SMA Negeri 1 Batang Kuis. Activities that have been implemented: Obtain permission from headmaster, measuring nutritional status, checking blood hemoglobin levels, carrying out counseling using LCD tools and booklets. Participants were 50 students from SMA N 1 Batang KuisThe implementation results showed that 22% of the female students' nutritional status was very thin and underweight, 20% of the female students' nutritional status was overweight and 22% of the female students were anemic. There was an increase in female students' knowledge about anemia by 3.52 points from 9.2 points before counseling to 12.72 points after counseling. Likewise, attitudes increased by 4.26 points from 50.78 points to 55.0 points. The resulting output: Published in the Community Service journal